O saxofone na música de câmara de Francisco Braga (Orfeu, 2021)
Abstract. From the works Cantiga e Danças dos pretos - for quartet of saxophones(1905) and 'Diálogo sonoro à luar' - seresta for alto saxophone and bombardino in C, byFrancisco Braga (S/D), in a succinct way, this article brings up the representativeness of thesaxophone in Francisco Braga's chamber repertoire. The text also argues about the composer'spioneering and language when writing for the instrument and, as a result, presents, based on thestudies by Oliveira (2019a) and Macedo (2019), significant aspects regarding Francisco Braga'srelations with the saxophone. In addition to observations on incongruous aspects regarding thecomposition date and other issues that permeate the 'Diálogo Sonoro ao Luar', there are alsonotes on the stylistic interfaces between the influence Ars Gallica and the genres, seresta,maxixe and habanera, based on the studies by Nascimento (2009), Soares (2015) and Cazes(2019).